Establishing a child-friendly village as a form of community awareness protection of child rights in Bedahlawak Village - Muhammad Firmansyah,; Tamara Sujarwo Putri,; Dipo Wahjono Haryono,; Muhammad Jufri Ahmad,; Abraham Ferry Rosando,; I Gusti Ayu Agung Noviekayati, (Technium Social Sciences Journal, 2022)
Children have a crucial involvement to sustain generations in a country. Therefore, the government and society must build awareness in terms of protecting children's rights. The environment for children should be able to provide conditions that are safe, peaceful and able to provide a balance for them. Currently the government is making efforts aimed at being able to provide a protection for children's rights in community experiencing obstacles. The research in this case uses a quantitative approach, namely an approach with data that has been obtained in questionnaires and numbers. With pre-test and post-test methods as a reference for the research team in order to assess the understanding of Bedahlawak community more accurately and can be a comparison with the situation before there is training. This activity can create a child-friendly village as a form of public awareness of the protection of children's rights in Bedalawak Village. A child-friendly village is a village development that includes combining the responsibilities and assets village government, local area, and business world to understand and fulfill the privileges of children. Protect children's families from violence, exploitation and abuse. Paying attention to children is strictly regulated in rule of law in Indonesia. Seeing by explanation above, in collecting basic needs children for develop and be creative, it is important to involve various associations, including: public authorities, local areas and secret areas through a program called the child-friendly city program, because children are a business. very big and very important later saved for improvement, if youth can now be framed with their capacity, then later it can become an asset for country that works to be more advanced. Likewise, it is important to highlight here of importance be family education, which although its implementation is for every family, basically this role is also surrounding environment. This family education, because the different practices of parents, is increasingly being neglected, and many parents are content to involve their children.